Heterogeneous ice nucleation ability of aerosol particles generated from Arctic sea surface microlayer and surface seawater samples at cirrus temperatures - Wagner, Robert; Ickes, Luisa; Bertram, Allan K.; Els, Nora; Gorokhova, Elena; Möhler, Ottmar; Murray, Benjamin J.; Umo, Nsikanabasi Silas; Salter, Matthew E. (Atmospheric Chemistry and Physics, 2021)
Sea spray aerosol particles are a recognised type of ice-nucleating particles under mixed-phase cloud conditions. Entities that are responsible for the heterogeneous ice nucleation ability include intact or fragmented cells of marine microorganisms as well as organic matter released by cell exudation. Only a small fraction of sea spray aerosol is transported to the upper troposphere, but there are indications from mass-spectrometric analyses of the residuals of sublimated cirrus particles that sea salt could also contribute to heterogeneous ice nucleation under cirrus conditions. Experimental studies on the heterogeneous ice nucleation ability of sea spray aerosol particles and their proxies at temperatures below 235 K are still scarce. In our article, we summarise previous measurements and present a new set of ice nucleation experiments at cirrus temperatures with particles generated from sea surface microlayer and surface seawater samples collected in three different regions of the Arctic and from a laboratory-grown diatom culture ( Skeletonema marinoi ). The particles were suspended in the Aerosol Interaction and Dynamics in the Atmosphere (AIDA) cloud chamber and ice formation was induced by expansion cooling. We confirmed that under cirrus conditions, apart from the ice-nucleating entities mentioned above, also crystalline inorganic salt constituents can contribute to heterogeneous ice formation. This takes place at temperatures below 220 K , where we observed in all experiments a strong immersion freezing mode due to the only partially deliquesced inorganic salts. The inferred ice nucleation active surface site densities for this nucleation mode reached a maximum of about 5×10 10 m −2 at an ice saturation ratio of 1.3. Much smaller densities in the range of 10 8 –10 9 m −2 were observed at temperatures between 220 and 235 K , where the inorganic salts fully deliquesced and only the organic matter and/or algal cells and cell debris could contribute to heterogeneous ice formation. These values are 2 orders of magnitude smaller than those previously reported for particles generated from microlayer suspensions collected in temperate and subtropical zones. While this difference might simply underline the strong variability of the number of ice-nucleating entities in the sea surface microlayer across different geographical regions, we also discuss how instrumental parameters like the aerosolisation method and the ice nucleation measurement technique might affect the comparability of the results amongst different studies.